PREVALENCE AND RELATED RISK FACTORS OF DIABETIC FOOT ULCERS AMONG PATIENTS WITH DIABETES IN SAUDI ARABIA: A CROSS-SECTIONAL STUDY (CAHIERS MAGELLANES-NS, 2024)
Background: Diabetic foot ulcers (DFUs) represent a chronic and severe complication of diabetes mellitus (DM), characterized by the deterioration of foot tissues in individuals affected by DM. Neuropathy is the most common cause of DFUs. The deleterious consequence of DFUs is amputation, which can significantly impair an individual’s quality of life. Numerous risk factors exist that increase the likelihood of diabetic individuals developing DFUs. These factors include inadequate glycemic control, foot deformities, improper foot care, and dry skin. Main objectives of this study are to determine prevalence and risk factors of DFUs among diabetic patients in Saudi Arabia.Methodology: A cross-sectional study that was scheduled to be carried out in Saudi Arabia among adult diabetic patients. All the patients diagnosed with either type 1 or type 2 diabetes who have provided their consent to participate in the research was incorporated. A structured questionnaire was used as a study tool. The questionnaire was validated and translated into Arabic language and tested by a pilot test after modification. The Raosoft calculator was utilized to determine the sample size which is minimum 384. The data was inserted by using the Microsoft Excel application (2023) then the data was transferred to the Statistical Package for the Social Science (SPSS) application, version 26, to undergo statistical evaluation.Results: Key findings include a predominant age range of 21-50, with higher female representation, diverse regional distribution, and a majority holding university degrees. The data highlights proactive diabetes management practices such as regular physician follow-ups and medication compliance. Associations were observed between DFU history and factors like gender, BMI, region, education level, and place of residence. Additionally, the presence of skin diseases, nail disorders, foot deformities, and walking barefoot outside showed significant correlations with foot ulcers. Family involvement in foot care, regular physical activity, and smoking habits also emerged as important factors influencing DFU prevalence. These results underscore the complex interplay of various factors in the development and prevention of diabetic foot ulcers.Conclusion: This cross-sectional study sheds light on the significant prevalence of diabetic foot ulcers (DFUs) among individuals with diabetes in Saudi Arabia, highlighting the associated risk factors and implications for public health. The study reveals a high prevalence of DFUs, with notable variations in prevalence rates across different age groups, genders, education levels, occupations, places of residence, smoking habits, and BMI categories. The findings underscore the importance of understanding and addressing these risk factors to develop targeted interventions and preventive measures to reduce the burden of DFUs and improve diabetes management in the country.